New Long-Term Braking Index Measurements for Glitching Pulsars Using a Glitch-Template Method - Espinoza-Romo, C (Oxford University Press, 2017)
Braking index measurements offer the opportunity to explore the processes affecting the longterm spin evolution of pulsars and possible evolutionary connections between the various pulsar populations. In most cases, such measurements are difficult because of the presence of short-term phenomena, such as glitches and timing noise, which obscure the long-term trends. In particular, recoveries from large glitches are the main obstacle to measuring the braking indices of young pulsars like the Vela and Crab pulsars. We present a new method to overcome this problem and report on braking index measurements for the Vela-like pulsars, PSR B1800-21 and PSR B1823-13, together with an updated measurement for Vela. Additionally, the use of the method is extended to six more young glitching pulsars observed at Jodrell Bank Observatory and we are able to estimate four new braking indices. Values of braking indices describe the long-term evolution of the pulsars across the P-P˙ diagram. Despite some measurements being affected by considerable uncertainties, there is evidence for a common trend among young glitching pulsars, characterized by low braking indices n ≤ 2. Such values introduce a new variant in the evolution of young pulsars, and their relationship with other populations in the P-P˙ diagram, and imply that these pulsars could be a few times older than indicated by standard formulae. In this context, we analyse the case of PSR B1757-24 and conclude that the pulsar could be old enough to be related to the supernova remnant G5.4-1.2. Between glitches, the short-term evolution of Vela-like pulsars is characterized by large interglitch braking indices nig > 10. We interpret both short- and long-term trends as signatures of the large glitch activity, and speculate that they are driven by short-term post-glitch re-coupling and a cumulative long-term decoupling of superfluid to the rotation of the star. © 2016 The Authors.